Análisis de la modernización en los procesos de contratación estatal en Colombia durante los años 2007 al 2011 (2012)
This essay intends to conduct an analysis of state modernization in the public area of government procurement, based on the reform in 2007 was Law 80 of 1993 with the issuance of the 1150 Act and its implementing regulations as the 2474 2008 to 2025 of 2010. Where they established new mechanisms for the procurement of goods and services to meet the needs of the state, based on compliance with the principles of transparency, economy and responsibility, and objective selection of the contractor, the same way as the procedure shown evolved state contracting.